Identifying Dust-Obscured Galaxy Candidates in SDSS Using a Colour–Extinction Approach - Yakubu, Mu’allim; Vwavware, Jude Oruaode; Ojobeagu, Austin Okechukwu; Ohwofosirai, Adrian (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
We present a systematic analysis of dust-obscured galaxy (DOG) candidates from a parent sample of ~50,000 galaxies in the Sloan Digital Sky Survey (SDSS). Using a selection method based on color and extinction thresholds, we identified 12,209 galaxies that represent a statistically significant population of dusty systems. These DOG candidates exhibit properties that are systematically different from the general SDSS galaxy population, including a higher mean redshift (z ≈ 0.35). Their average r-band extinction (Ar ≈ 0.145) significantly exceeds that of the broader sample (Ar ≈ 0.09), confirming enhanced dust attenuation. Our analysis of correlations between redshift and color indices reveals important evolutionary signatures. While color and redshift show a strong positive correlation, a notable negative correlation between extinction and redshift (ρ ≈ –0.59) suggests a geometric or physical evolution of dust. This study provides a foundational, purely optical baseline for isolating dusty galaxies in SDSS and sets the stage for future multi-wavelength research.